PERLINDUNGAN HUKUM BAGI REMAJA YANG MENJADI KORBAN SEXTORTION (SEKTORSI) - Sukma Riyanti Ningsih, Hana Cindar; Subekti, Subekti; Ayuningtiyas, Fitri; Prawesthi, Wahyu (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
The incidence of sextortion as a form of digital sexual violence is increasing in line with the development of information technology and the use of social media by teenagers. The characteristics of sextortion, which combines extortion with sexual exploitation, make it a crime with serious psychological, social and legal implications. However, the Indonesian criminal justice system does not yet have specific regulations governing this act, so law enforcement officials often charge perpetrators under general provisions in the Criminal Code, the Electronic Information and Transactions Law, the Pornography Law, and the Law on the Eradication of Sexual Violence. This normative gap raises the main research question: to what extent are existing regulations able to provide effective legal protection for adolescent victims of sextortion? This study aims to analyse the applicable legal framework, identify normative weaknesses in the handling of sextortion, and assess the extent to which victims’ rights are accommodated in national regulations. The research method used is a normative approach with a doctrinal legal research type. Legal materials were collected through a literature study covering legislation, academic literature, and scientific articles, then analysed qualitatively and descriptively with reference to legal protection theory and the principle of justice. The results of the study show that although there are a number of legal instruments that can be used, there is no single regulation that specifically regulates sextortion. The legal protection provided through the TPKS Law and the Witness and Victim Protection Law has granted important rights, such as restitution, compensation, and the right to be forgotten, but its implementation still faces normative and technical obstacles. This study contributes by emphasising the urgency of establishing specific regulations on sextortion to fill the legal void, strengthen victim protection, and expand preventive digital literacy. In conclusion, legal protection for victims of sextortion in Indonesia is still not optimal and requires more responsive criminal law reform. Further research is recommended to explore the effectiveness of implementing victims’ digital rights and psychosocial recovery mechanisms in the context of technology-based sexual violence.